Outbreak of Pseudomonas aeruginosa folliculitis associated with a swimming pool inflatable. - Tate, D. (Cambridge University Press, 2003)
On 18 February 2002, the Communicable Disease Unit was notified by the local Public Health Service Laboratory of a child with a positive skin swab for Pseudomonas aeruginosa. This child had attended the local swimming pool and played on an inflatable, subsequently presenting to a Primary Care Nurse Practitioner with folliculitis. A total of 35 cases was identified during the outbreak. This paper describes a case-control study and microbiological sampling of the cases, the suspected inflatable and a survey of 10 swimming pool inflatables in the local area. The odds ratio for developing folliculitis following use of the inflatable was 12 (95% CI 1.05-136.80). The strain of P. aeruginosa found on the inflatable was identical to that obtained from skin swabs of cases. Nine of 10 (90%) of the inflatables sampled were colonized by P. aeruginosa. Attention should be given to the problem of routine decontamination of swimming pool inflatables. P. aeruginosa folliculitis needs to be considered in the differential diagnosis of skin rashes in children, especially in Primary Care.